Rhesus incompatibility in pregnancy: a case report - Ali Sungkar; Raymond Surya (Indonesian Journal of Perinatology, 2020)
Introduction: Hemolytic disease of the fetus and newborn (HDFN) occurs due to the destruction of red blood cells, which the most common cause is rhesus incompatibility. This study aims to present a case of Rhesus incompatibility in pregnancy without a clinically significant effect on the baby. Case: A-38-years-old Indonesian woman with gravida 4 para 3 (G4P3A0), 32 weeks of gestational age came to the emergency department due to vaginal bleeding. On blood typing, she had an A-negative (A-) blood type. Her husband and all three of their children had O-positive (O+) blood type. The patient underwent a cesarean section due to recurrent antepartum hemorrhage following the total placenta previa. She gave birth to a baby girl, weighed 2,220 grams with an A-positive blood type. The hemoglobin level was 14.6 g/dL without any sign of neonatal jaundice during the first 24 hours of life. Conclusion: Our case illustrates a woman who did not show any sign of clinically Rhesus antigen alloimmunization. Low immunogenicity and dose-dependent response to a low fetal blood volume exposure might explain this phenomenon.